Providing Quality Of Service In IEEE 802.11 Wireless Local Area Network (WLAN) - Ng, Bryan Cheng Kuan (2005)
This thesis presents a novel quality of service (QoS)provisioning scheme for real-time applications in IEEE 802.IIe wireless local area networks (WLAN). The emerging 802.11e standard is tackling the exploding volume of traffic in WLANs with a long-term solution based on QoS-architectures. QoS delivers predictability and consistency into existing variability of best-effort delivery system offered in internet protocol (IP) and IEEE 802.11 wireless networks.